Disputing the ‘(Un)parliamentary’: Learning Rules of Debate in the Early Finnish "Eduskunta" (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The article examines the learning and adoption of international parliamentary rules and practices in the work of the Finnish parliament, the Eduskunta. The article concentrates on the rules of debate in the early Eduskunta and analyses how the character and quality of plenary speech was disputed within the framework of the Parliament Act of 1906 and the Eduskunta’s Rules of Procedure. By analysing debates of the early Eduskunta from 1907 and 1908 as well as Finnish newspaper material, the article illustrates how the learning and establishment of Finnish parliamentary practices evolved around disputes over the notions of ‘parliamentary’ and ‘unparliamentary’.